OVERVIEW OF ENGLISH LANGUAGE EDUCATION IN INDIA: HISTORY, POLICIES, TRENDS, AND PRACTICES - Naik, Tanmay M.; Shah, Sunil Kumar (ShodhKosh: Journal of Visual and Performing Arts, 2024)
English language education in India has seen a lot of changes since it was first used as a colonial tool to its more current role being that of an intellectual/cultural reclamation. During British rule, English was introduced to better control India but it replaced more local languages and values. The post-independence efforts were directed towards re-asserting the significance of Indian literary traditions in English Language Teaching (ELT) pedagogy which aimed at creating cultural pride and decolonising education. Emerging recent policies, such as the National Education Policy (NEP) 2020 advocate multilingualism and inclusivity in the form of Indian texts over Western text, modern pedagogical strategies. This ongoing evolution is indicative of the broader societal political changes in India where everything has been recalibrated to balance engagement with the wider world and native moorings.